The Evolution Of Research On Academic Cheating Behavior Based On The Theory Of Planned Behavior (TPB): Perspectives For Future Research - Respati, Yudit Ayu; Harsono, Mugi (Excellent, 2023)
This study aims to present a summary of various studies that explore academic cheating behavior with the support of a theory or conceptual framework so that it can be used as a valuable reference for monitoring the development of research on academic cheating behavior driven by the Theory of Planned Behavior (TPB). It is also hoped that this article can become a basis for inspiration for further research development in this domain in the future. The method applied in this study is a literature review using the connectedpapers.com platform. A search for relevant articles was conducted using the keywords "academic cheating behavior," "cheating behavior," and "academic misconduct." The study results show that the TPB can effectively predict academic cheating behavior. At the same time, variations in the use of variables include demographic, situational, and personality factors that are integrated with the TPB construct. The research methods used are also diverse, including a mixed-method approach.